PENDIDIKAN MULTIKULTURAL: SINERGITAS KEPEMIMPINAN ADAT MINANG-NIAS BERBASIS KEARIFAN LOKAL MEWUJUDKAN KONSENSUS - Arieska Dwi Asmil; Junaidi Indrawadi; Susi Fitria Dewi; Delmira Syafrini; Isnarmi Moeis (STKIP Singkawang, 2022)
The presence of two versions of leadership that are limited by differences in religion and customs in Korong Tanjung Basung II has an impact on the harmony that arises from the consensus that has been produced together. Based on this, this study aims to analyze how the management carried out by the traditional leaders of Nias and Minang based on local wisdom in realizing this harmony so as to make it an area with a fairly high understanding of multiculturalism. This type of research is a qualitative research using an ethnographic approach. The research location is in Korong Tanjung Basung II, Kanagarian Sungai Buluh Barat, Batang Anai District, Padang-Pariaman Regency, West Sumatra Province with research informants taken by snowball sampling technique. While the data collection techniques used in the form of observation, interviews, and documentation studies. To ensure that the data obtained are valid, data testing is carried out through source triangulation. Furthermore, the data were analyzed using data analysis techniques in the form of data reduction, data presentation, and drawing conclusions or verification. The results of the study indicate that in generating a common consensus, the interpersonal relationship between the ninik mamak and the Nias leader is the adoption of two systems of harmony by the traditional leaders of Nias and Minang. Ninik mamak uses the Bodi Chaniago system for the Minang community in generating consensus (through deliberation), while the Koto Piliang harmony system will be applied to the Nias community by presenting the Nias Leader as an intermediary for conveying and disseminating information, especially for the Nias ethnic group in KAN.